Upaya Penerapan Evaluasi Membaca Di Kelas Tinggi - Anggun Asri Winarti; Fachrizal Alwi; Lisa Sabina; Nurul Fatwa Sipayung; Ririn Indriani (Jurnal Pendidikan dan Sastra Inggris, 2023)
Reading is a cognitive activity or process that aims to find various information contained in written information. This means that reading is a thought process to understand the contents of the text read. Evaluation of learning to read is a series of activities or steps taken after the completion of the main activities to obtain information about the results of learning to read, then manage and interpret them using benchmarks and goals and certain criteria. This type of research is library research, namely research conducted by analyzing and making written literature scientific journals as well as the main source. So the evaluation of learning to read is the process of determining students’ understanding, acceptance, categorization, analysis and reasoning abilities, as well as the accuracy of students’ pronunciation and intonation when taking reading tests in the target language. The purpose of learning to read is so that students can understand and use language in practice, it is not enough to measure it with mere mechanical abilities. The assessment of reading ability must be seen from the general reading ability as a whole, so that when assessing skills other than mechanical skills, it is also necessary to measure reading ability, for example understanding the content or meaning of sentences. The purpose of this study is to find out how the effort to implement the evaluation of students’ reading learning.